Fire and land use impact soil properties in a Mediterranean dry sclerophyll woodland. (15th December 2022) - Ondik, Mercedes M.; Bennell, Michael; Davies, Richard J.-P.; Ooi, Mark K.J.; Muñoz-Rojas, Miriam
Abstract: Fire directly impacts soil properties responsible for soil function and can result in soil degradation. Across the globe, climate change-induced droughts and elevated temperatures are exacerbating fire regime severity, breadth, and frequency, thus posing a threat to soil function and dependent ecosystem services. In Australia, the 2019–2020 fire season consumed nearly 50% of Kangaroo Island, South Australia, burning both dry sclerophyll woodland and adjacent historically cleared and grazed pastureland. Due to exacerbated fire regime elements, e.g., intensity and area affected, and interactions with historical land use, post-fire recovery of soil function was uncertain. This study assessed the impacts of a) the 2019–2020 fire event in Western River, Kangaroo Island on dry sclerophyll woodland and b) the interaction between this fire event and historical clearing and grazing on post-fire function of the soil. To do so, the following physicochemical and biological soil properties were analysed: labile active carbon, total carbon, total nitrogen, carbon to nitrogen ratio (C/N), pH, electrical conductivity, soil water repellency, aggregate stability, microbial community composition, and microbial diversity. Our results showed that the fire was of high severity, causing a reduction in nutrient content, an extreme rise in pH, and significant modifications to fungal communities in burnt compared to unburnt dry sclerophyll woodland. Furthermore, clearing and grazing raised post-fire soil nutrient levels and soil microbial diversity but reduced soil C/N and the abundance of ectomycorrhizal fungi in burnt pastureland compared to burnt woodland soils. This study highlights the role of management and fire severity in post-fire outcomes and emphasizes the need for comprehensive soil function assessments to evaluate the impacts of disturbance on soil. Taking direct measure of soil properties, as done here, will improve future assessments of fire season impacts and post-fire recovery in fire-prone landscapes. Highlights: Fire severity and historical land use impact post-fire outcomes on soil function. High severity fire reduced soil nutrients and soil water repellency. Clearing and grazing raised soil nutrient levels but lowered the soil C/N ratio. Clearing and grazing reduced pH and the relative abundance of ectomycorrhizal fungi. Both fire and management impacted microbial community composition and diversity.